Countermeasures to Improve Road Alignment Consistency of Undivided Rural Roads - Francesca Russo; Salvatore Antonio Biancardo (The Baltic Journal of Road and Bridge Engineering)
The research aims to assess the relationships between the crash rates and road consistency. Design consistency  assessment is a tool employed by designers to improve road safety. The case study involved a rural two-lane two-way  road in Southern Italy located on a flat terrain without spiral transition curves between tangent segments and circular  curves. Road alignment consistency was examined in two steps: by adopting standards in force in Italy based on the  design speed profile and by plotting operating speed profile to determine the area bounded by the speed profile and the  average weighted speed, and the standard deviation of operating speeds for each geometric segment. Operating speed  prediction model, which returns the 85th percentile of the speed distribution of the only cars under free flow conditions,  right weather conditions, and lighting was adopted. A negative exponential function was performed to predict  the global consistency of a road as a whole. Finally, a model for predicting the crash rate was calibrated, confirming an  increase of design consistency when the crash rates decrease significantly. The consistency model represents a useful tool during the geometric design process or the evaluation process for two-lane rural highways.